2009
DOI: 10.1007/s00299-009-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

An abiotic stress-responsive bZIP transcription factor from wild and cultivated tomatoes regulates stress-related genes

Abstract: Wild relatives of cultivated tomato (Solanum lycopersicum) are resistant to a wide range of abiotic and biotic stress conditions. In an effort to understand the molecular mechanisms of salt stress resistance in the wild and cultivated Solanum species, a basic leucine zipper (bZIP) transcription factor was identified in S. chilense, S. peruvianum and S. lycopersicum and named ScAREB1, SpAREB1 and SlAREB1, respectively. Deduced amino acid sequences of the three proteins are 97% identical among them and present h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 40 publications
6
78
0
Order By: Relevance
“…AREBs were recognized to be engaged in response to abiotic stress in Solanum genus (Yanez et al 2009). It was reported that the expression of TF encoding gene, SlAREB, in tomato and tobacco leaves upregulated the expression of stress-responsive genes, including the LEA genes, RD29B gene and trehalose-6-phosphate phosphatising gene.…”
Section: Transcription Factors (Tfs)mentioning
confidence: 99%
See 1 more Smart Citation
“…AREBs were recognized to be engaged in response to abiotic stress in Solanum genus (Yanez et al 2009). It was reported that the expression of TF encoding gene, SlAREB, in tomato and tobacco leaves upregulated the expression of stress-responsive genes, including the LEA genes, RD29B gene and trehalose-6-phosphate phosphatising gene.…”
Section: Transcription Factors (Tfs)mentioning
confidence: 99%
“…It was reported that the expression of TF encoding gene, SlAREB, in tomato and tobacco leaves upregulated the expression of stress-responsive genes, including the LEA genes, RD29B gene and trehalose-6-phosphate phosphatising gene. In further studies, it was proved that genetically modified tomato plants with overexpression of SlAREB1 showed improved tolerance to water and salt stress (Yanez et al 2009;Hsieh et al 2010;Orellana et al 2010). Similarly, the cytokinin response factors (CRFs), a subgroup of AP2/ERF transcription factors, were shown to take part in tomato response to diverse abiotic stresses, including oxidative, flooding, osmotic, temperature and drought ones.…”
Section: Transcription Factors (Tfs)mentioning
confidence: 99%
“…bZIP TFs are important in the response of plants to abiotic stress (Yáñez et al, 2009). In Arabidopsis, this TF family has been divided into ten (A-I and S) groups according to their DNAbinding domain (Jakoby et al, 2002).…”
Section: Group a Members Of Bzip Tfs In Carrotmentioning
confidence: 99%
“…The basic-region/leucine-zipper (bZIP) TF family, for example, performs significant functions in resisting abiotic stresses (Yáñez et al, 2009). The bZIP TFs are one of the most conserved proteins present in all eukaryotes (Riechmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the native species Solanum chilense (Dunal) Reiche, with proven tolerance to several abiotic stress conditions (Maldonado et al, 2003;Venema et al, 2005;Tapia, 2005;Yáñez et al, 2009) becomes as potential germplasm source.…”
mentioning
confidence: 99%